Nutrition and Rheumatic Disease - Coleman, Laura A. (Nutrition and Health, 2008)
It is difficult, if not impossible, for health care providers to remain at the forefront of knowledge for all aspects of nutrition and rheumatic diseases. In Nutrition and Rheumatic Disease, experts provide a comprehensive review of current knowledge regarding nutrition and dietary management for the complex set of rheumatic conditions. Within the disease-specific chapters, the authors present a historical perspective, a discussion of the major clinical features, current management and treatment, a review of the literature related to nutritional status and diet, and dietary recommendations, based on current scientific evidence. The field of rheumatic diseases includes a wide variety of pathologic processes. Adequate reviews of the scientific literature on each of the rheumatic diseases in Nutrition and Rheumatic Disease alleviate the inherent confusion surrounding the risks and benefits of various dietary therapies.